SP1/AKT/FOXO3 Signaling Is Involved in miR-362-3p-Mediated Inhibition of Cell-Cycle Pathway and EMT Progression in Renal Cell Carcinoma - Zhu, Hejia; Wang, Song; Shen, Haixiang; Zheng, Xiangyi; Xu, Xin (Frontiers in Cell and Developmental Biology, 2020)
Emerging evidence has indicated that dysregulation of miR-362-3p is involved in the initiation and progression of several types of human cancers. However, the molecular mechanism of miR-362-3p in renal cell carcinoma (RCC) is still not completely clear. In this study, we found that miR-362-3p was frequently down-regulated in human RCC tissues. Overexpression of miR-362-3p in RCC cells significantly suppressed the proliferation, cell cycle and motility in vitro and in vivo via regulating AKT/FOXO3 signaling. We further confirmed that SP1 was a direct target of miR-362-3p. Knockdown of SP1 expression by a small interfering RNA (siRNA) phenocopied the effect of miR-362-3p overexpression in RCC cells. In conclusion, the current results provide evidence for the role of miR-362-3p in the pathogenesis of RCC and thus miR-362-3p may serve as an attractive candidate for RCC therapy.